Religious Extremism and Terrorism In The Evaluation Of The Mass Consciousness Of The Student Youth (Socio-Psychological analysis On The Example Of almaty) (The Journal of Psychology and Sociology, 2019)
The topic of this study is “Religiouspolitical extremism in assessing the mass consciousness of the youth of Almaty city”. The main objective of this work is to reveal the factors and conditions of the development and coping with religious and political extremism in the context of globalization, in particular in the Republic of Kazakhstan. The main directions and ideas of scientific research will be achieved by solving the following tasks: to provide accurate religious and political extremism; the protection of the factors and the social base of extremist behaviour with the account of ethnical and confessional measurements; and to suggest methods of the prophylaxis and resistance of religiouspolitical and political extremism on the basis of a structural analysis.The object of the research was students of Almaty aged 18 years and older, having a temporary or permanent registration. The main results and conclusions of this study: the results of the survey show that the majority of the surveyed residents aged 18 years and older position themselves as believers. Nevertheless, the analysis shows that 25% of students admit that they are unbelievers atheists or agnostics. In the society of students, it is necessary to spread the idea that each person has the right to decide religious issues within the limits permitted by law, based on his constitutional rights. No one has the right to “shame” a person for his faith or disbelief, or the choice of a religious denomination. The value of the study lies in the fact that its results on the prevention and counteraction of religiouspolitical extremism can be considered as the basis for further studying the place and role, condition and specificity of religious extremism, and its significance lies in deepening and expanding knowledge about countering religious extremism in the context of globalization. The practical significance of the study seems to be that, to prevent the political radicalization of religiouspolitical extremism, consistent work is needed on the sociopolitical activity of believers.Key words: religion, extremism, mass media, religiouspolitical extremism.